Health and performance of trypanotolerant cattle breeds exposed to quantified trypanosomiasis risk at five sites within the African Trypanotolerant Livestock Network - Maehl, H.M.; Coulibaly, L.; Defly, A.; D'Ieteren, G.D.M.; Dumont, P.; Feron, A.; Grundler, G.; Itty, P.; Jeannin, P.; Leak, S.G.A.; Morkramer, G.; Mulungo, M.; et al. (OAU/STRC, 1988)
A study of tsetse populations and the health and performance traits of one or more trypanotolerant cattle breeds (N'Dama, Baoule and race locale) at five sites in West and Central Africa between 1983 and 1986